PENGARUH KEBISINGAN LALU LINTAS TERHADAP AKTIVITAS BELAJAR MENGAJAR DI GEDUNG V UNIVERSITAS SEMARANG - Fahrudin Ahmad; Roni Kartika Pramuyanti; Erlinasari; Kukuh Wisnuaji Widiatmoko (Faculty Of Engineering University 17 August 1945 Semarang, 2024)
Noise in educational environments can affect the effectiveness of teaching and learning processes. This study aims to analyze the impact of traffic noise on teaching and learning activities in Building V of Semarang University, located along the Soekarno-Hatta arterial road. The research method uses a qualitative descriptive approach by measuring noise levels using a Sound Level Meter on six floors of the building. Measurements were taken during active lecture hours with time intervals of 3 x 30 minutes. The results showed that noise levels on floors 1 to 3 were above the educational environment quality standard of 55 dB according to KepMenLH No. 48 of 1996. Meanwhile, on the 6th floor, the noise level averaged around 55 dB. Excessive noise makes it difficult for students to hear lecturers' explanations, reduces their ability to capture information, and decreases learning material retention. To address these issues, sound insulation installation, spatial planning improvements by designing room layouts farther from noise sources, vegetation planting, and lecture rescheduling to avoid peak traffic times are necessary.